1983
DOI: 10.1037/0022-0167.30.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics anxiety: Some basic issues.

Abstract: The study investigated four basic questions about mathematics anxiety: (a) the degree of math anxiety experienced by men and women; (b) the internal consistency and test-retest reliabilities of three math anxiety measures; (c) the relationship of math anxiety instruments to each other; and (d) the relationship of math anxiety to test anxiety and its worry and emotionality components. The subjects were 769 students at the University of North Carolina at Greensboro. Math anxiety was measured by Fennema and Sherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 9 publications
2
66
1
3
Order By: Relevance
“…Correlations of about .70 have been reported between the MAS and the 98-item Mathematics Anxiety Rating Scale (Cooper & Robinson, 1991). Dew, Galassi, and Galassi (1983) reported Cronbach's alpha of .72 and 2-week test-retest reliability of .87. Hackett and Betz (1989) reported Cronbach's alpha values ranging from .86 to .90.…”
Section: Methodsmentioning
confidence: 99%
“…Correlations of about .70 have been reported between the MAS and the 98-item Mathematics Anxiety Rating Scale (Cooper & Robinson, 1991). Dew, Galassi, and Galassi (1983) reported Cronbach's alpha of .72 and 2-week test-retest reliability of .87. Hackett and Betz (1989) reported Cronbach's alpha values ranging from .86 to .90.…”
Section: Methodsmentioning
confidence: 99%
“…Dew, Galassi, and Galassi (1983), Fox (1997) and Alexander and Matray (1989) found evidence of gender differences in the levels of math anxiety reported by students A distinction has been drawn by Rounds and Hendel (1980) between anxiety concerning maths and an anxiety concerning the testing of maths.…”
Section: Barriers To Skill Developmentmentioning
confidence: 99%
“…It is still important to note that in their study, Dew et al (1983) provided evidence that mathematics anxiety and test anxiety are related and suggested that mathematics anxiety is a subject specific of test anxiety.…”
Section: Mathematics Anxiety and Its Connection To Test Anxietymentioning
confidence: 99%
“…Many researchers have related mathematics anxiety to test anxiety; suggesting that mathematics anxiety may be similar to test anxiety (Brush, 1981, Hembree, 1990, Dew, Galassi & Galassi 1983. Hembree (1990) suggested that mathematics anxiety is similar to test anxiety, in that both relate to general anxiety, both affect performance in similar ways, both respond to same types of treatment modes, and both types of anxiety are relieved when performance improves.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation